Fruit shading enhances peel color, carotenes accumulation and chromoplast differentiation in red grapefruit. Issue 4 (4th March 2015) - Lado, Joanna; Cronje, Paul; Alquézar, Berta; Page, Anton; Manzi, Matías; Gómez‐Cadenas, Aurelio; Stead, Anthony D.; Zacarías, Lorenzo; Rodrigo, María Jesús
<x xml:space="preserve">Abstract</x> The distinctive color of red grapefruits is due to lycopene, an unusual carotene in citrus. It has been observed that red 'Star Ruby' (SR) grapefruits grown inside the tree canopy develop a more intense red coloration than those exposed to higher light intensities. To investigate the effect of light on SR peel pigmentation, fruit were bagged or exposed to normal photoperiodic conditions, and changes in carotenoids, expression of carotenoid biosynthetic genes and plastid ultrastructure in the peel were analyzed. Light avoidance accelerated chlorophyll breakdown and induced carotenoid accumulation, rendering fruits with an intense coloration. Remarkably, lycopene levels in the peel of shaded fruits were 49‐fold higher than in light‐exposed fruit while concentrations of downstream metabolites were notably reduced, suggesting a bottleneck at the lycopene cyclization in the biosynthetic pathway. Paradoxically, this increment in carotenoids in covered fruit was not mirrored by changes in mRNA levels of carotenogenic genes, which were mostly up‐regulated by light. In addition, covered fruits experienced profound changes in chromoplast differentiation, and the relative expression of genes related to chromoplast development was enhanced. Ultrastructural analysis of plastids revealed an acceleration of chloroplasts to chromoplast transition in the peel of covered fruits concomitantly with development of lycopene crystals and plastoglobuli. In this sense, an accelerated differentiation of chromoplasts may provide biosynthetic capacity and a sink for carotenoids without involving major changes in transcript levels of carotenogenic genes. Light signals seem to regulate carotenoid accumulation at the molecular and structural level by influencing both biosynthetic capacity and sink strength.